Eicosanoids in carcinogenesis - Brücher Björn L.D.M.; Jamall Ijaz S. (4 open, 2019)
Inflammation is the body's reaction to pathogenic (biological or chemical) stimuli and covers a burgeoning list of compounds and pathways that act in concert to maintain the health of the organism. Eicosanoids and related fatty acid derivatives can be formed from arachidonic acid and other polyenoic fatty acids via the cyclooxygenase and lipoxygenase pathways generating a variety of pro- and anti-inflammatory mediators, such as prostaglandins, leukotrienes, lipoxins, resolvins and others. The cytochrome P450 pathway leads to the formation of hydroxy fatty acids, such as 20-hydroxyeicosatetraenoic acid, and epoxy eicosanoids. Free radical reactions induced by reactive oxygen and/or nitrogen free radical species lead to oxygenated lipids such as isoprostanes or isolevuglandins which also exhibit pro-inflammatory activities. Eicosanoids and their metabolites play fundamental endocrine, autocrine and paracrine roles in both physiological and pathological signaling in various diseases. These molecules induce various unsaturated fatty acid dependent signaling pathways that influence crosstalk, alter cell–cell interactions, and result in a wide spectrum of cellular dysfunctions including those of the tissue microenvironment. Although the complete role of eicosanoids, including that of the recently elucidated anti-inflammatory specialized pro-resolving lipid mediators (SPMs), e.g. lipoxins, resolvins, protectins and maresins, is not completely understood, the result of unremitting chronic inflammation is fostering early stages of carcinogenesis. Chronic inflammation facilitates the transition from a normal cell to a cancerous one. The disruption of homeostasis across a wide, but identifiable, swath of diverse molecular pathways creates a micromilieu which constitutes an early and necessary step in the 6-step sequence of carcinogenesis for the vast majority of cancers, termed “sporadic cancers”.